Comparison of routine and microwave-assisted decalcification of bone with or without teeth: A histologic study - Niloofar Hajihoseini; Gita Rezvani; Shahroo Etemad-Moghadam (Wolters Kluwer Medknow Publications, 2020)
Background: The aim of this study was to compare conventional and microwave-assisted decalcification of sheep bone with and without teeth and to detect any difference in tissue detail preservation, staining quality, and rate of decalcification. Materials and Methods: In this method analysis study, twenty-four specimens consisting of 12 blocks of mandibular molars with their surrounding bone and 12 blocks of mandibular osseous tissue were allocated into two microwave or routine decalcification groups using 5% nitric or formic acid as decalcifying agents. In addition to decalcification rate, a number of variables were used to assess staining quality and tissue detail preservation which were compared between the two groups using Mann-Whitney test (P < 0.05). Results: Time to complete decalcification was significantly reduced in the microwave-treated samples as compared to the conventional method, regardless of the decalcifying agent (P = 0.025). For both acids, most variables related to staining quality and tissue detail preservation were similar between the techniques (P > 0.05). Patchy staining in bone samples and tissue tears in bone + teeth specimens were more common in the routine method when using nitric acid (NAc) (P = 0.046) and formic acid (FAc) (P = 0.046), respectively. In comparing acids, the performance of FAc was slightly inferior to that of NAc, especially for specimens containing both tooth and bone. Conclusion: The use of microwave technology can accelerate decalcification of bone and teeth of sheep mandibles and at the same time preserve tissue structure and staining quality. Further studies are required to help select the best demineralizing agent, especially in specimens containing bone and teeth.